Assessing community engagement in Nigeria polio eradication initiative: application of the Consolidated Framework for Implementation Research. Issue 8 (9th August 2021) - Akinyemi, Oluwaseun Oladapo; Adebayo, Adedamola; Bassey, Christopher; Nwaiwu, Chioma; Kalbarczyk, Anna; Fatiregun, Akinola A; Alonge, Olakunle O.; Owoaje, Eme
Abstract : Objective: This study employed the Consolidated Framework for Implementation Research (CFIR) to assess factors that enhanced or impeded the implementation of community engagement strategies using the Nigerian polio programme as a point of reference. Design: This study was a part of a larger descriptive cross-sectional survey. The CFIR was used to design the instrument which was administered through face-to-face and phone interviews as well as a web-based data collection platform, Qualtrics. Setting: The study took place in at least one State from each of the six geopolitical zones in Nigeria (Nasarawa, Borno, Kano, Sokoto, Anambra, Bayelsa, Lagos, Ondo and Oyo States as well as the Federal Capital Territory). Participants: The respondents included programme managers, policy-makers, researchers and frontline field implementers affiliated with the Global Polio Eradication Initiative (PEI) core partner organisations, the three tiers of the government health parastatals (local, state and federal levels) and academic/research institutions. Results: Data for this study were obtained from 364 respondents who reported participation in community engagement activities in Nigeria's PEI. Majority (68.4%) had less than 10 years' experience in PEI, 57.4% were involved at the local government level and 46.9% were team supervisors. Almost half (45.0%) of the participants identified the process of conducting the PEI program and social environment (56.0%) as the most important internal and external contributor to implementing community engagement activities in the community, respectively. The economic environment (35.7%) was the most frequently reported challenge among the external challenges to implementing community engagement activities. Conclusion: Community engagement strategies were largely affected by the factors relating to the process of conducting the polio programme, the economic environment and the social context. Therefore, community engagement implementers should focus on these key areas and channel resources to reduce obstacles to achieve community engagement goals.